A literary and historical analysis of Ephesians 5:18-6:9 - Cress, Shana (St. Louis, Missouri : Covenant Theological Seminary, 2018)
1 online resource (PDF (ix, 69 leaves)); Abstract; Thesis (M.A.E.T.)--Covenant Theological Seminary, 2018; Bibliography: leaves 66-69